Properties and tribological performance of ceramic-base chromium and vanadium carbide composite coatings. (June 2019) - Günen, Ali; Kurt, Bülent; Milner, Piers; Gök, Mustafa Sabri
Abstract: In the current study, the surface of AISI D2 steel was coated with the powder blends of ferro-vanadium (Fe-V) and ferro-chromium (Fe-Cr). The coatings were performed using a thermo-reactive diffusion (TRD) treatment by the pack cementation method at three different temperatures (900 °C, 1000 °C, and 1100 °C) and three different durations (1 h, 2 h, and 3 h). The structural and mechanical characteristics of the coatings were compared between the treatment groups. For this aim, the types of the formed phases, the microstructure, the microhardness, the surface roughness, and the wear and friction performance of the coated samples were examined. XRD analysis found composite carbide coatings including chromium carbide (Cr-C), vanadium carbide (V-C), and chromium vanadium carbide (Cr-V-C). The coatings' thickness was 11.3–23.2 μm, hardness was 2100–2500 HV, and average surface roughness (Ra ) was 0.286–0.550 μm, depending on the treatment condition. The vanadium containing phase contents of the coatings increased with the elevating coating temperatures. The formed composite coating layers caused a change in the appearance of wear track and wear mechanism on the material surface. After the coating process, there found to be a decrease in the friction coefficient as well as an improvement in the wear resistance up to 7 times. In the composite coating layers, the increase in V-C content in comparison to Cr-C led to an enhancement in wear resistance on the material surface. Highlights: Composite coating was first time successfully produced on a steel by powder pack TRD. Advantageous influences of composite coatings on mechanical properties were observed. Elemental distribution at the coating layers affected the hardness and wear rate. The wear resistance increased up to 7 times due to the formation of hard CrVC phases. Transition in wear behavior was observed with change in treatment conditions.